A Purified Resin Glycoside Fraction from Pharbitidis Semen Induces Paraptosis by Activating Chloride Intracellular Channel-1 in Human Colon Cancer Cells - Zhu, Dongrong; Chen, Chen; Xia, Yuanzheng; Kong, Ling-Yi; Luo, Jianguang (Integrative cancer therapies, 2019)
Pharbitidis Semen has worldwide recognition in traditional medicine for the treatment of several illnesses apart from its purgative properties, and it is also reported to show anticancer effect. However, limited pharmacological studies are available on the extract or resin glycosides fraction of Pharbitidis Semen. The purpose of this study was to determine the mechanism of the colon cancer cell cytotoxic effect of a purified resin glycoside fraction from Pharbitidis Semen (RFP). Our results showed that the RFP-induced cell death was mediated by the caspase-independent and autophagy-protective paraptosis, a type of cell death that is characterized by the accumulation of cytoplasmic vacuoles and mitochondria swelling. RFP significantly stimulated endoplasmic reticulum stress, inhibited proteasome-dependent degradation, and activated the MAPK signaling pathway in human colon cancer cell lines. Furthermore, we found that RFP activated chloride intracellular channel-1 (CLIC1) and increased the intracellular Cl− concentration. Blockage of CLIC1 by DIDS (disodium 4,4′-diisothiocyanato-2,2′-stilbenedisulfonate hydrate) attenuated cell death, cytoplasmic vacuolization, and endoplasmic reticulum stress, suggesting that CLIC1 acts as a critical early signal in RFP-induced paraptosis. In conclusion, results obtained indicated that the cytotoxic effect of RFP in colon cancer cells was the outcome of paraptosis mediated by activation of CLIC1.